Value of Testing at 30°C for the Identification of Cold Alloantibodies in the Presence of Cold Autoantibodies - Wu, MD, PhD, Ding Wen; Hsu, MD, Peihong; Freeman, MT(ASCP), SBB, Jane (North American Journal of Medicine and Science, 2012)
Acute hemolytic transfusion reaction due to hemolytic anti-Lea is a rare phenomenon. We present here a case report of an acute hemolytic transfusion reaction, and demonstrated that an additional procedure of incubation at 30˚C facilitated the identification of a hemolytic anti- Lea in this diagnostic challenged case. A 46 year old man with a history of AIDS and dementia presented with symptomatic anemia. During transfusion of the 2nd unit of packed RBCs, the patient experienced high fever, back pain and dark brown urine. The blood bank and laboratory workup revealed evidence of a quickly resolved acute intravascular hemolysis. Other causes of intravascular hemolysis were ruled out with various laboratory tests. Initial blood bank antibody workup revealed a cold auto-anti-I, and a cold allo-antibody of undetermined specificity. Tests at 30˚C were described by Lawrance Petz and George Garratty for workup of cold auto-antibodies at 30˚C. We extrapolated their method to clearly identify a hemolytic anti-Lea with broad thermal amplitude. Phenotyping and crossmatching at 30˚C revealed that the 1st unit was implicated in the acute hemolytic transfusion reaction. This is the first report to successfully identify a hemolytic anti-Lea using the method at 30˚C for cold allo-antibody workup.